Ultrafast spectroscopy tracks carotenoid configurations in the orange and red carotenoid proteins from cyanobacteria - Šlouf, Václav; Kuznetsova, Valentyna; Fuciman, Marcel; de Carbon, Céline Bourcier; Wilson, Adjélé; Kirilovsky, Diana; Polívka, Tomáš (Photosynthesis research, 2017)
A quenching mechanism mediated by the orange carotenoid protein (OCP) is one of the ways cyanobacteria protect themselves against photooxidative stress. Here, we present a femtosecond spectroscopic study comparing OCP and RCP (red carotenoid protein) samples binding different carotenoids. We confirmed significant changes in carotenoid configuration upon OCP activation reported by Leverenz et al. (Science 348:1463-1466. doi: 10.1126/science.aaa7234 , 2015) by comparing the transient spectra of OCP and RCP. The most important marker of these changes was the magnitude of the transient signal associated with the carotenoid intramolecular charge-transfer (ICT) state. While OCP with canthaxanthin exhibited a weak ICT signal, it increased significantly for canthaxanthin bound to RCP. On the contrary, a strong ICT signal was recorded in OCP binding echinenone excited at the red edge of the absorption spectrum. Because the carbonyl oxygen responsible for the appearance of the ICT signal is located at the end rings of both carotenoids, the magnitude of the ICT signal can be used to estimate the torsion angles of the end rings. Application of two different excitation wavelengths to study OCP demonstrated that the OCP sample contains two spectroscopically distinct populations, none of which is corresponding to the photoactivated product of OCP.
Keywords: spektrální analýza; Intramolecular charge-transfer state; Non-photochemical quenching; Orange carotenoid protein; Ultrafast spectroscopy; Cyanobacteria; sinice; karotenoidy; Spectrum Analysis; Carotenoids; Red carotenoid protein